Assessment of factors affecting the intensity of adoption, production, and consumption of biofortified crops in Mazowe district - Kambarami. Tinashe C. (BUSE, 2022)
More than 2 billion people suffer from hidden hunger globally due to inadequate intake of micronutrient rich diets. Zimbabwe is not spared from this predicament as it is battling recurring food insecurity challenges which have been exacerbated by climate change and its adverse effects. In Zimbabwe on average 22% of the general population are Vitamin A deficient and 65% iron deficient as such efforts to combat these deficiencies have been adopted through the food systems approach. Most studies on biofortified crops have focused on adoption leaving a gap on production and consumption hence this study aims to bridge the gap between factors affecting adoption, intensity of production and consumption. The study was conducted in Mazowe district with focus on ward 12. From a sampling frame of 300 households that was availed by the Agritex officer responsible for the ward, the researcher interviewed 183 randomly selected respondents. A household questionnaire was administered at household level to collect survey data. Descriptive statistics, binary regression analysis and linear regression analysis were used in the analysis of data. A lesser proportion of households (17.5%) had adopted and were cultivating biofortified crops at the time the survey was conducted whilst 82.5% had not adopted. Adoption of bio fortified crops was significantly influenced by contact with agricultural extension services, knowledge and area of arable land a household had access to. The intensity of production was affected by income a household had access to monthly and area of arable land that can be accessed whilst consumption was mostly affected by health consciousness, knowledge and social networks within the community. It is key for households to have a revolving fund that will help in boosting agricultural activities at household level through purchase of seeds, fertilizers and other key inputs. The misconception between GMOs and biofortified crops portrays a knowledge gap and this calls for awareness campaigns at national and subnational level so that consumers are capacitated. At policy level there is need to mainstream and incorporate the biofortified crops in the educational curriculum so that people are informed from grass root level upwards on the importance of these crops to human health. Keywords: Adoption, Biofortification, Consumption, Deficiency, Production, Vitamin
Keywords: Biofortified crops; Biofortification